Impact Assessment of the Public Health Expenditure on the Health Outcome in Nigeria - Eboh, Alfred; Abba, Justina Yachat; Fatoye, Helen Ajibike (International Journal of Social and Administrative Sciences, 2018)
This study is conceived mainly to assess the impact of the public health expenditure on the infant mortality rate in Nigeria. The study made use of an ex-post facto research design and time series data spanning the period of twenty-four years (1994-2017). The data covered the Health Recurrent Expenditure (HRE), the Health Capital Expenditure (HCE) and Infant Mortality Rate (IMR) in Nigeria sourced the Central Bank of Nigeria statistical bulletin 2016 and the World Bank report. Descriptive statistics were used to analyse the data while Ordinary Least Square (OLS) technique was used to estimate the model. The study revealed that both the HRE and the HCE by the government of Nigeria had a significant negative effect on the Infant Mortality Rate (IMR) for the period of 24 years under review. Similarly, HRE had a more significant negative effect on the infant mortality rate than the HCE in this study. The authors, therefore, concluded that the Nigerian government at various levels should spend adequate funds on all the tiers of health care system in order to promote efficiency and effectiveness of the health sector. By so doing, it might lead to a phenomenal reduction in the current infant mortality rate in the country.